Endoscopic Findings of Dyspeptic Patients and H. pylori infection in patients at a Tertiary care Teaching Hospital, Nepal - Subedi, Dharma Datta; Shrestha, Muza (Janaki Medical College Journal of Medical Science, 2023)
Introduction: Dyspepsia is a common condition presenting with epigastric pain that lasts at least a month and may develop peptic ulcers. Helicobacter pylori infection and lifestyle are the risk factors for peptic ulcers. So, the objective of this study was to identify the magnitude and status of Helicobacter pylori in dyspeptic patients. Material and Methods: This cross-sectional study included data from the endoscopy unit records among patients who had endoscopy for dyspepsia and biopsy taken from an antrum for the helicobacter pylori status, during June 1, 2020 and November 30, 2022 at Manmohan Memorial Medical College Teaching Hospital, Kathmandu, Nepal. Age, sex and status of histopathology findings were analyzed for association using Chi-square test and a p<0.05 was considered statistically significant. Results: Among 439 dyspeptic patients, 297 (67.7 %) had positive finding of PUD. In all investigated patients, H. pylori positive was 297(67.7%) and negative in 142(32.3 %). The mean age was 45.42 y (17 - 82), 267 (60.8%) males and 172 (39.2%) females, 33(7.5 %) had a gastric ulcer and 55(12.5%) had duodenal ulcer. Duodenal ulcers were seen in younger age (17-39 y) and gastric ulcer in older age (> 60 y) with p-value <0.0001. Gastric malignancies were found in 6 (1.4%). Conclusion: The occurrence of H. pylori with dyspeptic patients was high. Peptic ulcers were more common in young age and males than in females. Duodenal ulcers were more common than gastric for both sexes.